2020 ASEE Virtual Annual Conference Content Access Proceedings
DOI: 10.18260/1-2--34695
|View full text |Cite
|
Sign up to set email alerts
|

From Q&A to Norm & Adapt: The Roles of Peers in Changing Faculty Beliefs and Practice

Abstract: is a learning scientist and associate professor at the University of New Mexico in the Organization, Information & Learning Sciences program and in the Chemical & Biological Engineering Department. She served as Co-PI on an NSF RET Grant and a USDA NIFA grant, and is currently co-PI on three NSF-funded projects in engineering and computer science education, including a Revolutionizing Engineering Departments project. She was selected as a National Academy of Education / Spencer Postdoctoral Fellow and a 2018 N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Our chemical engineering degree includes a 1-credit first-year course, four core technical courses, as well as laboratory, seminar, and concentration-specific courses, culminating in a two-semester capstone design sequence (see Figure 1). Some of the faculty were hesitant about the curricular changes (Ferris et al, 2022;Gallup et al, 2020;. We viewed this as expected, in part because we recognized that in their educations, they had not experienced such approaches.…”
Section: Contextmentioning
confidence: 96%
See 1 more Smart Citation
“…Our chemical engineering degree includes a 1-credit first-year course, four core technical courses, as well as laboratory, seminar, and concentration-specific courses, culminating in a two-semester capstone design sequence (see Figure 1). Some of the faculty were hesitant about the curricular changes (Ferris et al, 2022;Gallup et al, 2020;. We viewed this as expected, in part because we recognized that in their educations, they had not experienced such approaches.…”
Section: Contextmentioning
confidence: 96%
“…Given that many of our first-generation and low-income students had abundant opportunities having to "make do" and "make it work, " our faculty readily agreed that these kinds of experiences were valuable. We share more detailed examples of how we collaborated with faculty elsewhere (Davis et al, 2021;Gallup et al, 2020;Kang et al, 2022;Svihla, Chi, et al, 2022).…”
Section: Assessing Needmentioning
confidence: 99%
“…Many change projects fail to bring about change [17,18]; complicating this, what counts as evidence of sustained successful change is poorly defined. However, our prior work also suggested that by supporting faculty to implement sociotechnical design challenges in core classes, faculty became more aware of student potential, because such teaching brought them into closer proximity with students and such experiences brought out students' passion [19]. We argue that the 2020 pandemic, which brought about an abrupt shift to teaching online, provided a fair test of faculty beliefs and revealed a great deal about their values related to student learning.…”
Section: Purpose Of This Studymentioning
confidence: 77%
“…Some of the design challenges were co-designed with graduate students who worked in industry, vetted by the department's industry advisory board, or developed with significant input from industry sponsors. Along with shifting to design-focused courses, the faculty collaborated with a learning scientist and attended workshops to develop learner-centered teaching strategies, results of which are reported elsewhere [26][27][28][29][30][31]. Over this timespan, several faculty discarded prior challenges or significantly revised their design challenges, before being pleased with the student outcomes.…”
Section: Nondeterministic High Ceilingmentioning
confidence: 99%